WACANA KOMUNIKASI PESANTREN DI ERA REVOLUSI INDUSTRI 4.0 - Kun Wazis (Indonesian Journal of Islamic Communication, 2020)
The Development of communication science in increasingly dynamic. The phenomena of health communication studies, tourism communication, corruption communication, for example, strengthen the position of communication science. The study tried to explain pesantren communication as a new study in communication studies. This paper examined through a qualitatif descriptive approach with a literature study that focussed on two important aspect, namely communication and Islamic boarding school (pondok pesantren). The study of communication has a dimension to analysis reality based on messages or symbols displayed in human interaction, like on Islamic boarding school community. Beside that, Islamic boarding schools community showed many messages to interpreted by communition study. The result of this study indicated that communication has the ability to interpreted many symbols or message on Islamic boarding community. And, Islamic boarding school as social change institution displays symbol or message that must be studied by communication studies. Pesantren communication can be categorized into a new variant in communication studies.